Handbook of Engaged Sustainability (Springer International Publishing, 2018)
This handbook is based on the premise that in order for sustainability to be sustainable, a profound psychological transformation has to take place at the individual and collective level. Focusing on the practice of environmental sustainability, this handbook will explore the application of sustainability in a wide variety of contemporary contexts-from economics of consumption and growth to government policy, sustainable cities, and sustainable planet. The editors believe that the way to achieve sustainable, harmonious living in all spheres is through lived or engaged sustainability at the personal, team, and organizational levels. It is impossible to separate economic development issues from environment issues. In its most practical aspect, sustainability is about understanding the interconnections among environment, society, and economy. This book aims to provide a comprehensive overview of current theories and approaches in the area of engaged sustainability for academics, researchers and practitioners. Specifically, it will focus on making responsible decisions that will reduce humanity's negative impact on the environment. While various social and political initiatives for sustainability are welcome, one cannot really enact sustainability into legislative laws. Something has to change fundamentally at the level of a common person in the street. The Handbook of Engaged Sustainability acknowledges the classic literature, theories and principles in the area of sustainability, but also provides new theories and approaches from global scholars and practitioners in the field. It will also provide a well-structured pedagogical framework with real life case examples. The aim of this handbook is to expand the reader's thinking to one of "big-picture awareness" and a "cosmic vision" of sustainability, a vision that extends from our neighborhoods to our communities, to states, countries, globe, galaxy, and envelops the entire Universe! This book will serve as an essential resource for researchers, scholars and students of sustainability, ethics, corporate social responsibility and environmental economics, as well as consultants, business and team leaders, and anyone interested in engaged sustainability. .